1974
DOI: 10.2466/pr0.1974.35.2.763
|View full text |Cite
|
Sign up to set email alerts
|

Authoritarianism, Occupational Sex-Typing, and Attitudes toward Work

Abstract: This study explored the relationships between authoritarianism, work motivation, and occupational sex-role typing. There was a direct positive relationship between high F scores, extrinsic work motivation, and rigid occupational sex-role typing and between low F scores, intrinsic work motivation and flexible occupational sex-role typing. The way in which this directly affects men's perceptions about women at work is discussed. The study presented here explores a constellation of personality traits and attitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1976
1976
1986
1986

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Whenever the nature of a subject's stated advantage or disadvantage was unclear to the interviewer, the subject was questioned further until the advantage or disadvantage was fully clarified. The use of advantages and disadvantages to tap intrinsic and extrinsic job motives (introduced in Slotnick & Bleiberg, 1974) precluded the problems inherent in using a preselected set of factors.…”
Section: Methodsmentioning
confidence: 99%
“…Whenever the nature of a subject's stated advantage or disadvantage was unclear to the interviewer, the subject was questioned further until the advantage or disadvantage was fully clarified. The use of advantages and disadvantages to tap intrinsic and extrinsic job motives (introduced in Slotnick & Bleiberg, 1974) precluded the problems inherent in using a preselected set of factors.…”
Section: Methodsmentioning
confidence: 99%
“…Johnson, Johnson, and Martin (1961) found that authoritarian subjects from entrepreneurial backgrounds were more restrictive than nonauthoritarians in the number of behaviors that they considered appropriate to children of both sexes. Slotnick and Bleiberg (1974) administered the Occupational Sex-Typing Scale to male college students. High authoritarians rated significantly more occupations as sex-linked and relegated inferior job positions to females while reserving decisionmaking jobs for males.…”
mentioning
confidence: 99%